Expression of Sox transcription factors in the developing mouse pancreas. - Wegner, Michael; et al. (Developmental Dynamics, 2003)
Previous work has identified members of the homeodomain and basic helix-loop-helix families of transcription factors as critical determinants of mammalian pancreatic development. Here, we describe the identification of HMG-box transcription factors of the Sox gene family in the mouse pancreas. We detected transcripts for Sox11, Sox4, Sox13, Sox5, Sox9, Sox8, Sox10, Sox7, Sox17, Sox18, Sox15, and Sox30 in embryonic pancreas and found Sox4, Sox9, and Sox13 in adult pancreatic islets. Expression of seven of these Sox factors was studied in more detail by in situ hybridization from the stage of early pancreatic outgrowth to birth. Expression of Sox11 was found in the mesenchyme surrounding the pancreatic buds, whereas Sox4 and Sox9 were confined to the pancreatic epithelium and later to islets. Sox13 and L-Sox5 showed expression in most of the pancreatic epithelial cells between embryonic days 12.5 and 14.5. Sox8 and Sox10 were detected in a thin layer of cells surrounding the islets. The expression patterns of Sox genes in the embryonic pancreas suggest that they could have important and possibly redundant functions in pancreas development. © 2003 Wiley-Liss, Inc.
UnivIS-Import:2015-04-14:Pub.2003.med.IB.LPCIPDBI.expres
Keywords: Development; Embryo; Glucagon; Insulin; Islet; Mouse; Pancreas; Sox; Transcription factor